Integration of Islamic Religion and Character Education with Environmental Education at Adiwiyata Junior High School - Gita Anggraini; Muhibbin Syah; Asep Nursobah; Bambang Samsul Arifin (Syntax Corporation Indonesia, 2022)
Islamic religious education and environmental education have the same goal. The purpose of Islamic religious education and character education in schools is to create students who have good relationships with God, themselves, fellow human beings, and nature. Not much Islamic religious education integrates environmental education. Adiwiyata school is an environmental culture school that integrates environmental education in learning, including PAI. This study aims to identify the integration of PAI and Character with environmental education in Adiwiyata schools. The research locus is SMP Negeri 1 Sampit. The research was conducted using a qualitative approach with descriptive methods and case studies.